From betaines to anionic N-heterocyclic carbenes. Borane, gold, rhodium, and nickel complexes starting from an imidazoliumphenolate and its carbene tautomer - Liu, Ming; Namyslo, Jan C.; Nieger, Martin; Polamo, Mika; Schmidt, Andreas (Beilstein Journal of Organic Chemistry, 2016)
The mesomeric betaine imidazolium-1-ylphenolate forms a borane adduct with tris(pentafluorophenyl)borane by coordination with the phenolate oxygen, whereas its NHC tautomer 1-(2-phenol)imidazol-2-ylidene reacts with (triphenylphosphine)gold(I) chloride to give the cationic NHC complex [Au(NHC)2][Cl] by coordination with the carbene carbon atom. The anionic N-heterocyclic carbene 1-(2-phenolate)imidazol-2-ylidene gives the complexes [K][Au(NHC−)2], [Rh(NHC−)3] and [Ni(NHC−)2], respectively. Results of four single crystal analyses are presented.
Keywords: anionic ligand; carbene tautomer; imidazol-2-ylidene; mesoionic compound; mesomeric betaine